The relationship between interest rate and inflation towards exchange rate volatility in Malaysia/ Nurmadihah Jusoh - Jusoh, Nurmadihah (Faculty of Business and Management, 2010)
This paper examines the relationship between the exchange rate volatility in Malaysia and its factors; interest rate and inflation rate using Johansen cointegration analysis based on ECM. The relationship among those variables is investigated using monthly data from 1999 to 2009. The researcher focused on that particular period of study because the researcher wants to know how strong the Malaysia Ringgit after the currency crisis in 1997. After having completed the analysis by using Vector Error Correction Model (VECM), the findings shows that interest rate has positive relationship with the exchange rate volatility while inflation rate has negative relationship in the long run. On the other hand, Granger causality resulted that there is unidirectional from interest rate to inflation rate and from inflation rate to exchange rate changes in the short run.